2017
DOI: 10.1088/1741-4326/aa6187
|View full text |Cite
|
Sign up to set email alerts
|

Strong suppression of impurity accumulation in steady-state hydrogen discharges with high power NBI heating on LHD

Abstract: Strong suppression of impurity accumulation is observed in long pulse hydrogen discharges with high power NBI (Neutral Beam Injection) heating (P nbi > 10 MW) on the Large Helical Device (LHD), even in impurity accumulation window where the intrinsic impurities such as Fe and C are always accumulated into the plasma core. Density scan experiments in these discharges demonstrate a new operational regime without impurity accumulation in steady state hydrogen discharges. Impurity pinch decreases with increasing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In LHD, the impurity transport is quite sensitive to the collisionality of the plasma. 27 Moreover, a recent LHD experiment revealed that the strong gradient of the electron density causes the outward transport of impurities. 28 Then it is possible that impurity ions in the core plasma are transported to the outward direction by the formation of the steep electron density gradient by the ablation of the pellet.…”
Section: Discussionmentioning
confidence: 99%
“…In LHD, the impurity transport is quite sensitive to the collisionality of the plasma. 27 Moreover, a recent LHD experiment revealed that the strong gradient of the electron density causes the outward transport of impurities. 28 Then it is possible that impurity ions in the core plasma are transported to the outward direction by the formation of the steep electron density gradient by the ablation of the pellet.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, recently observed discrepancies between modeled and experimental light impurity radial profiles at the ASDEX Upgrade (AUG) and JET tokamaks are challenging the current theoretical understanding [11][12][13]. Indeed, in regimes where the normalised ion temperature and toroidal rotation gradients are large and where transient transport mechanisms such as sawteeth and edge localised modes (ELM) are negligible, theory does not quantitatively predict the experimental negative boron/carbon peaking factors (hollow profiles) and in some cases even predict peaked profiles instead [11,13,14]. A more detailed experimental analysis of the diffusive and convective parts of the boron flux performed at AUG for low NBI heating cases (≤ 5 MW) [15] showed good agreement with the modelling results [16].…”
Section: Introductionmentioning
confidence: 99%
“…The situation is completely different in stellarators. Experimentally, stellarator impurity accumulation in the plasma core is consistently observed [11] (although there are remarkable, not completely understood, exceptions like the "impurity hole" [12,13] in the Large Helical Device (LHD) and the "High Density H mode" in Wendelstein 7-AS [14]; see also [15] for another exception in LHD involving plasmas with higher density than those typical of the impurity hole). Impurity accumulation leads to fuel dilution and even to plasma termination by radiative collapse.…”
Section: Introductionmentioning
confidence: 99%